The effect of Online Costumer Reviews and Influencer Marketing on Shopee Purchasing Decisions - Muhammad Fachmi; Sinau, Hasriani (Terbuka Journal of Economics and Business, 2022)
The purpose of this research id to determine the partial and simultaneous effect of the variables studied. In this research using quantitative research approach with a sample number of 99 students with multiple regression analysis methodes spss aplikasi assistance 25. This research was conducted at (Case Study of Undergraduate Students) STIE Amkop Makassar. The purpose of this research shows that from the results of data management using the SPSS 25 application, it is known that that there is a positive and significant effect of online customer review on purcashing decision, and so is partial teasting of influencer marketing on meaningful perfomance of positive and significant effect, while simultaneous testing shows that online customer review and influencer marketing have a positive and significant effect on perfomance